Analisis Dampak CSR Disclosure pada Nilai Perusahaan di Era ESG: Studi pada Industri Manufaktur - Bahtiar Effendi (Politeknik Ganesha Medan, 2025)
Firm value is one of the most important indicators for evaluating a company's performance and attractiveness to investors. The sustainability of a company is not solely determined by financial indicators, but also by how well the company fulfills its social and environmental responsibilities. This study aims to examine whether Corporate Social Responsibility Disclosure (CSRD) influences firm value. The sample of this research consists of manufacturing companies listed on the Indonesia Stock Exchange during the period 2023–2024. This is a quantitative study using a purposive sampling method. The data analysis techniques include classical assumption tests, descriptive statistics, multiple linear regression analysis, and hypothesis testing. The results indicate that CSRD has a positive and significant effect on firm value. These findings support legitimacy theory, which posits that companies gaining public legitimacy through good social and environmental performance will enhance corporate image, attract investors, and ultimately increase firm value. Furthermore, the study also provides empirical support for agency theory, suggesting that CSR disclosure can reduce information asymmetry between management and stakeholders. This research is expected to serve as a reference for future studies by incorporating additional variables such as environmental performance or corporate governance as moderating variables.